An investigation of conflict and conflict resolution in the 2009 teachers strike in Soweto public schools - Kenosi, Carthage Tony (My University, 2011)
This study investigates conflict and conflict resolution in the 2009 SADTU strike in SOWETO public schools. It is an attempt to contribute to the understanding of the phenomenon of wildcat strike which presents itself as a significant problem in industrial relations. The study showed that a wildcat strike is characterized by underlying factors which tend to be the long term causes of the strike, the immediate causes of the strike and the strike trigger. These are followed by other processes such as violence during the strike, mediation, conciliation and finally the conclusion of the conflict. This study was conducted in SOWETO where the wildcat strike under investigation took place. This was a qualitative study using one-on-one interviews and semi-structured questions. The respondents composed of SADTU site stewards, School Principals, Officials from the Gauteng Department of education, the Gauteng Department of Labour, Officials from COSATU and union leaders from SADTU, NEHAWU, NACTU and NUM. The involvement of the union in the decision making process is characterized by a lot of controversy especially when it comes to filling of promotional posts for deserving educators. Unions abdicate their observer status and demand to be key decision makers despite this being the sole responsibility of the Department of education officials. This research illuminates the realities of using schools as places where the broader social, economic and political conflicts are often played out. The study revealed that having access to union power gives one an opportunity to be promoted. Those who are promoted do end up as government officials within the education department, resulting in virtually every current government official in the education department having been a SADTU official in the past.
M.A. Faculty of Humanities, University of the Witwatersrand, 2011